A late fourth‐ to early third‐millennium grave from Bahrain, c.3100–2600 BC. (11th October 2013) - Laursen, Steffen Terp
<x xml:space="preserve">Abstract</x> This article presents an exceptional burial that was excavated in 1986 by the National Museum of Bahrain. The presence of two 'Jemdat Nasr' style ceramic vessels in the grave makes it a unique testimony of occupation on Bahrain Island in the late fourth to mid‐third millennium BC. A local cooking vessel also uncovered from the grave represents the earliest local pottery production so far uncovered in Bahrain.